HUBUNGAN EMOTIONAL COPING BEHAVIOR DENGAN AGRESIVITAS SUPORTER SEPAK BOLA BONEK MANIA - Syaiba, Abdulloh Alba (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2021)
The study would like to see the relationship of emotional coping behavior with the aggressiveness of bonek mania soccer supporters. This research is a correlational quantitative study. The sample used in this study is 197 bonek mania supporters selected through a simple random sampling technique. The research instrument was a way of coping scale for the emotional-focused coping scale and an aggression questionnaire scale for the aggressiveness scale. Pearson's Product Moment Analysis on SPSS version 2.2 for Windows shows a correlational value of 0.271 with a significance value of 0.000 (<0.05). The results indicate that there is a correlation between emotional coping behavior and aggressive Bonek Mania.